DECISION SUPPORT SYSTEM FEASIBILITY OF GRANTING RECEIVABLES ON GOODS EXPORT SERVICES IN FREIGHT FORWARDING COMPANY WITH PROFILE MATCHING METHOD - sebastian, Ivan; Jumaryadi, Yuwan; Kusumawardani, Ratna; Setiawan, Bayu (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2021)
Decision Support System (DSS) is a system that is able to provide problem solving skills in both semi-structured and unstructured ways. The company's role in the import-export business is very important because it can meet the needs of people who have been doing business in the trade sector, both domestic trade and international trade. Indonesia as a country with a high volume of international trade requires a transportation service company that can support goods export activities by providing payment facilities with a certain time period. The problem that occurs is that there are customers who experience congestion in payment of receivables. This is because there is no standardized procedure in determining the granting of receivables so that it is difficult to determine the feasibility of granting receivables to customers. Therefore, researchers will conduct research on a decision support system with the profile matching method to determine the feasibility of granting receivables to goods export services by applying the 5C principle so that decision makers do not use intuition again and have methods or standardized procedures in providing receivables to customers. This research is expected to help determine the feasibility of receivables by applying the 5C principle, it is hoped that it can help decision makers in making decisions about giving credit to customers.